Glanzmann’s Thrombastenia: The Role of Tranexamic Acid in Oral Surgery - Rocco Franco; Michele Miranda; Laura Di Renzo; Antonino De Lorenzo; Alberta Barlattani; Patrizio Bollero (Case Reports in Dentistry)
Glanzmann’s thrombastenia (GT) is the most frequent inherited condition. GT is a genetic autosomal recessive disease caused by the alteration of the genes ITGA2B and ITGB3, located on the chromosome 17. The incidence of GT is calculated in 1 on 1000000. The patients, during their life, show episodes of mucocutaneous bleeding, epistaxis, and gingival bleeding. Some subjects required continuous bleeding transfusion. The aim of this case report is to demonstrate that oral assumption of tranexamic acid is a gold standard to prevent excessive bleeding. The patient GM of 36 years old with GT type 1 needs dental extractions of the teeth 4.7 and 4.8 at the “Tor Vergata” University Hospital in Rome. The specialist suggests that 3 days before surgery, the patient must take 6 vials every day of tranexamic acid that is used in obstetrics and gynecology. The teeth were extracted and applied suture. The patient is observed and is recommended mouth rinse with tranexamic acid. No bleeding complications were observed.